2017
DOI: 10.1007/s13346-017-0399-y
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo permeation of erythropoietin through porcine conjunctiva, cornea, and sclera

Abstract: The aim of this study is to test the permeation of human recombinant erythropoietin (rHuEPO) across conjunctiva, cornea, and sclera in an ex vivo model. Thirty fresh pig eyes were collected from a slaughterhouse. Conjunctivas (n = 10), corneas (n = 10), and scleras (n = 10) were surgically dissected from surrounding tissues. Ocular membranes were placed into Franz diffusion cells and rHuEPO was administered into the donor phase of each cell, except for control samples. Samples were collected from the receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…They also concluded that scleral permeability decreased with increasing molecular weight and the molecular radius [22]. We have previously demonstrated that rHuEPO can permeate porcine conjunctiva, sclera, and corneas in an ex vivo model [30]. Since glaucoma is a chronic disease, multiple treatments to protect RGCs are required, and using the subconjunctival route seems to be more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…They also concluded that scleral permeability decreased with increasing molecular weight and the molecular radius [22]. We have previously demonstrated that rHuEPO can permeate porcine conjunctiva, sclera, and corneas in an ex vivo model [30]. Since glaucoma is a chronic disease, multiple treatments to protect RGCs are required, and using the subconjunctival route seems to be more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The value of Jss of the PGZ in cornea and sclera were similar for free drug. The PGZ from NSs permeates less through the cornea than sclera, showing that the cornea has a barrier effect three times higher than the sclera (30). This is a consequence of the cornea having a regular cellular order, while the cells of the sclera have a more irregular cellular arrangement (31).…”
Section: Ex Vivo Permeation Studiesmentioning
confidence: 96%
“…The study is translational to clinical practice in that it reminds us that EPO therapy is a double-edged sword in the treatment of eye disease. Different modes of EPO administration, such as systemic delivery or intravitreal injection, have given positive results for ocular disorders [ 2 , 36 , 37 ]. There is emerging evidence for the neuroprotection effect of EPO both in vivo and in vitro [ 21 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%